Increasing Ability to Recognize Letters Through Animation Media in Children Aged 5-6 Years in Kindergarten: Peningkatan Kemampuan Mengenal Huruf Melalui Media Animasi Pada Anak Usia 5-6 Tahun di Taman Kanakkanak - Ayunda, Ervina Nela; Aulina, Choirun Nisak (Indonesian Journal of Education Methods Development, 2023)
The ability to recognize letters is the first step for children to be able to read, the ability to recognize letters well then the child tends to have the ability to read well too. This research is a classroom action research, with the object of Group B TK Dharma Wanita Persatuan Plaosan totaling 12 children. The writing of this study aims to determine the ability to recognize letters and the results of their improvement. Data collection techniques were carried out by means of observation, interviews and documentation. This research was conducted in 3 cycles, namely pre-cycle, cycle I and cycle II. Based on the results of the research that has been done, it can be seen that with animation media, the ability to recognize letters in children can be improved well with a significant increase in each cycle. The percentage value obtained in the first cycle reached a percentage of 56.5% but had not reached the success target, therefore it was carried out again in the second cycle which achieved a success percentage of 82.2%. Thus, it can be concluded that there is an increase in the ability to recognize letters through animation media in Dharma Wanita Persatuan Plaosan Kindergarten with a percentage reaching 82.2%.